False Memories in Native and Foreign Languages - Dolgoarshinnaia, Aleksandra; Martin-Luengo, Beatriz (Frontiers in Psychology, 2021)
Human memory is prone to memory errors and distortion. Evidence from studies on cognitive functions in bilinguals indicates that they might be prone to different types of memory errors compared to monolinguals, however, the effect of language in false memories is still understudied. Source monitoring processes required for proper memory functioning, presumably, rely on inhibitory control, which is also heavily utilized by bilinguals. Morevoer, it is suggested that thinking in a second language leads to more systematic and deliberate reasoning. All these results lead to expect that bilinguals are more analytical when processing information in their second language overcoming some memory errors depending on the language of information. To test this hypothesis, we run a classical misinformation experiment with explicit source monitoring task with a sample of Russian-English bilinguals. The language of misinformation presentation did not affect the degree of the misinformation effect between Russian and English languages. Source monitoring demonstrated overall higher accuracy for attributions to the English source over the Russian source. Furthermore, analysis on incorrect source attributions showed that when participants misattributed the sources of false information (English or Russian narrative), they favored the Russian source over the not presented condition. Taking together these results imply that a high proficiency in the second language do not affect misinformation and that information processing and memory monitoring in bilinguals can differ depending on the language of the information, which seems lead to some memory errors and not the others.